Pengaruh Jamur Tiram dan Lama Fermentasi Terhadap Karakteristik Fisik Biofoam Sabut Kelapa dan Pulp Kopi - Dedy Rahmad; Dian Hasni; Dwi Kemala Putri; Addin Akbar; Kushisa Atta Jaeba (Politeknik ATI Padang, 2025)
The urge to develop more sustainable foam for food packaging is increasing due to the high potential danger of the usage of Styrofoam as food packaging. This study aimed to determine the physical qualities of bio-foam, which was prepared using Pleurotus ostreatus F2 as the fungal microorganisms and the composite of coconut fiber and coffee pulp as substrates. This research was designed as Randomized Complex Block Design with two factors and four repetitions. The ANOVA results showed that both independent factors and their interactions have a very significant effect on the density, porosity, water absorption, and biodegradability of the resulting bio-foam. The higher percentage of Pleurotus ostreatus F2 added (60%) tended to produce bio-foam with lower density, porosity, and water absorption compared to the lower percentage (50%). However, prolonged fermentation up to 5 days tended to increase density, porosity and water absorption of bio-foam. Resulted biofoam has potential to be used as food packaging with further improvement to strengthen the matrix and enhance ethe water absorption quality.